Performance enhancement of the photovoltaic module using a semicircular serpentine channel with binary fluids mixture. Issue 2 (26th January 2023) - Deshmukh, Vipul; Kumar, Rajan; Tyagi, Praveen Kumar
ABSTRACT: The photovoltaic (PV) cells have a good capability for large-scale power generation. However, it is also true that the electrical conversion efficiency/electrical efficiency ( η e l e ) of the PV cell is relatively low compared to power generation by non-renewable energy sources. The issue with the PV cell is its low η e l e which further reduces with the rise in the average temperature of the PV module (TPV module ). An active cooling approach is adopted in this study to reduce the rising TPV module . The experimental work examines the effect of the serpentine semicircular channel installed at the back of the PV module. Water and a binary fluid mixture of acetone and methanol with water as the base fluid are employed as working fluids. The concentration of the binary fluid mixture is 1, 2, and 5 wt.% in the base fluid. The study revealed that the average increase in the η e l e of the PV module with 1 wt.% acetone-based binary fluid is 15.79% compared to the stand-alone uncooled PV module, and average enhancement in the η e l e for PV module with water cooling is 12.93% compared to the PV module without cooling facility. The average increase in the η e l e of the PV module with 5 wt.% methanol-based binary fluid cooling is observed to be 7.73% as compared to uncooled PV module, and the maximum average thermal efficiency η t h is enhanced by 17.47% for the 1 wt.% acetone-based binary fluid as compared to water-based cooling.